Increased Temporal Dynamics of Intrinsic Brain Activity in Sensory and Perceptual Network of Schizophrenia - Zhang, Youxue; Guo, Gang; Tian, Yuan (Frontiers in Psychiatry, 2019)
Schizophrenic subject is thought as a self-disorder patient related with abnormal brain functional network. It has been hypothesized that self-disorder associated with the deficient functional integration of multisensory body signals in schizophrenic subjects. To further verify this assumption, fifty-three chronic schizophrenic subjects and sixty-seven healthy subjects were included in this study, and underwent resting-state functional magnetic resonance imaging (fMRI). The data-driven methods, whole brain temporal variability of fractional amplitude of low frequency fluctuations (fALFF) and regional homogeneity (ReHo), were used to investigate dynamic local functional connectivity and dynamic local functional activity changes in schizophrenic subjects. Patients with schizophrenia exhibited increased temporal variability ReHo and fALFF across time windows within sensory and perception network (such as occipital gyrus, precentral and postcentral gyri, superior temporal gyrus and thalamus). Critically, the increased dynamic ReHo of thalamus is significantly correlated with positive and total symptom of schizophrenic subjects. Our findings revealed that deficit in sensory and perception functional networks might contribute to neural physiopathology of self-disorder in schizophrenic subjects.